2017
DOI: 10.1051/matecconf/201712006011
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of shallow foundations on geogrid reinforced soil

Abstract: Abstract.Geogrids have been increasingly used as soil improvement technique over the past decade. This increasing trend is attributed to its ease of application and low cost compared to other improvement techniques. This paper provides a review of the published results related to the ultimate and allowable bearing capacities of shallow foundations on geo-grid-reinforced homogeneous sand soil. A numerical analysis is also conducted to investigate soil-geogrid interaction considering several critical parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The results also showed that the beneficial effects of reinforcement at a low settlement ratio (s/B) can be achieved maximally when the top layer spacing is less than 0.25B. Alternatively, Arab et al [27] conducted a numerical analysis on the strip footing supported by sandy soil by using a…”
Section: Mechanism Of Geogrid Reinforcementmentioning
confidence: 99%
See 2 more Smart Citations
“…The results also showed that the beneficial effects of reinforcement at a low settlement ratio (s/B) can be achieved maximally when the top layer spacing is less than 0.25B. Alternatively, Arab et al [27] conducted a numerical analysis on the strip footing supported by sandy soil by using a…”
Section: Mechanism Of Geogrid Reinforcementmentioning
confidence: 99%
“…Alternatively, Arab et al . [ 27 ] conducted a numerical analysis on the strip footing supported by sandy soil by using a hardening soil model. They reported that for the geometrical parameters u / B = h / B = 0.5, and b / B = 4, the effect of the increasing number of geogrid layers ( N ) on the bearing capacity of the geogrid reinforced soils increased the bearing capacity and slightly increased the overall stiffness of the reinforced sand.…”
Section: Mechanism Of Geogrid Reinforcementmentioning
confidence: 99%
See 1 more Smart Citation
“…A soil's bearing capacity is influenced by properties such as shear strength [19]. Dense sand has a higher bearing capacity than loose sand due to its density [20]. A shallow foundation is used when the soil's bearing capacity is sufficient to safely support the structure's load [21].…”
Section: Introductionmentioning
confidence: 99%